Global, regional, and national burden of acute glomerulonephritis from 1990 to 2021 and future trend predictions until 2036: a systematic analysis using the Global Burden of Disease Study 2021 - Jiao, Yangtian; Chen, Xing; Zhang, Tianyu; Ma, Changyu; Shen, Congrong; Yu, Bo (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to analyze the global, regional, and national burden of acute glomerulonephritis (AGN) from 1990 to 2021 and project its trends through 2036 using data from the Global Burden of Disease (GBD) study.MethodsUsing the GBD 2021 dataset, we evaluated the burden of AGN in terms of incidence, mortality, and disability-adjusted life years (DALYs). Age-standardized rates (ASRs) were calculated, and trends were assessed using the Estimated Annual Percentage Change (EAPC) measure. Decomposition analysis quantified the contributions of population growth, aging, and epidemiological changes. Projections for AGN burden were modeled using the Auto-Regressive Integrated Moving Average (ARIMA) approach.ResultsFrom 1990 to 2021, the global age-standardized incidence rate (ASIR) of AGN declined by 46.09%, and the age-standardized DALY rate decreased by 65.87%. Middle-Socio-Demographic Index (SDI) regions exhibited the highest burden, while high-SDI regions showed increasing trends in mortality and DALY, potentially linked to autoimmune and systemic conditions. Decomposition analysis highlighted the role of epidemiological improvements, balanced by the impacts of population growth and aging. Projections indicate a continued global decline, with a 43.81% reduction in the ASIR and a 62.92% decline in the age-standardized DALY rate by 2036.ConclusionDespite significant global progress, disparities persist, particularly in low- and middle-income regions. Targeted interventions, enhanced diagnostic capabilities, and strategies that address socioeconomic determinants are essential to achieving a equitable reduction in the AGN burden. This study emphasizes the importance of global and regional strategies in improving AGN outcomes worldwide.